Authenticity predicts positive interpersonal relationship quality at low, but not high, levels of psychopathy. (November 2021) - Seto, Elizabeth; Davis, William E.
Abstract: Authentic self-expression is associated with many positive well-being outcomes, but do these benefits persist when the self being expressed is callous and malevolent? Across two studies (total N = 866), we tested the extent to which the relationship between authenticity and the quality of interpersonal relationships was moderated by Dark Tetrad personality traits. An exploratory study ( N = 380) indicated that psychopathy significantly moderated the relationship between authenticity and self-esteem, depression, hostility, and rocky relationships. A subsequent preregistered confirmatory study ( N = 486) replicated exploratory findings for both hostility and rocky relationships. Authenticity was associated with positive interpersonal relationship quality (less rocky relationships and less hostility) when psychopathy was low, but not when psychopathy was high. These findings highlight a significant way in which the relationship between authentic self-expression and well-being may depend upon the personality traits being expressed. Highlights: Psychopathy moderates the link between authenticity and interpersonal well-being. Authenticity predicts positive interpersonal relationships at low psychopathy. Authentic expression of psychopathy may impair interpersonal relationship quality.